Restriction of the right to constitutional and judicial protection in Russian practice - Malyutin, Nikita S. (Journal of the Belarusian State University. Law, 2024)
The article analyses a complex change in legislation in the field of constitutional control, which allows us to talk about the formed restrictive understanding of the constitutional right to judicial protection in relation to its constitutional procedural form. In particular, the right to access to constitutional justice is studied in its historical development from the moment it was enshrined in the Constitution of the Russian Federation of 12 December 1993 to the present, and the institutional changes that have taken place in the system of domestic constitutional control are also evaluated. Special attention is paid to the novelties of the Federal Constitutional Law of 9 November 2020 No. 5-ФКЗ « On amendments to the Federal Constitutional Law “On the Constitutional Court of the Russian Federation”», which fixed a number of provisions that can be considered as tools for restricting the relevant right to constitutional and judicial protection. The author critically assesses the judicial reform that has taken place in this part and offers his own options for correcting the current situation. As a result, the author states the current approach to the restrictive interpretation of the right to constitutional and judicial protection, in connection with which he proposes its systematic scientific understanding and the need for adjustment.